Strategy Of Achieving Quality Assurance Of Full Day SchoolIn SDIT Ar Rahmah Pacitan - Sumiati, Endang, Dr.Muindinillah Basri, M.A, Dr.Syamsul Hidayat, M.Ag (2013)
SDIT Ar Rahmah Pacitan employe full day school as a way to develop the students potentiality. Quality assurance is offered to increase the trust of the society of the demand of good education. This study aims at (1) Describing the implementation of full day school in SDIT Ar Rahmah Pacitan, (2) Describing the strategy in achieving quality assurance in SDIT Ar Rahmah pacitan, and (3) Describing the problem occurred and the solution. This study uses qualitative approach, a method used to observe the condition of natural object, in which the researcher acts as the key instrument. The method used to determine the subject is purposive sampling. The techniques of collecty data are observation, structured and unstructured interview, and documentation. After collecting the data, the researcher analyzed them describtively and inductively by using data reduction procedure, data categorizing, data synthesizing, and concluding. The result of this research is the implementation of full day school model in SDIT Ar Rahmah Pacitan in employing the student character building habit, academically and non academically. The strength of this model is that school has adequate time to implement the program. There are two weakness of this model, first, both the students and the teachers feel bored and it needs serious solution to manage it. Second, full day school system reduces the time with the family. The strategy in achieving quality assurance can be done by focusing on the quality of the students achievement, a comphrehensive monitoring of students achievement, improvement analysis, and commitment. The problem occord in achieving the quality assurance is the weakness of the method used, the solution offered wastering the method of quality achievement, for example Brainstorming, network affinity, Ishikawa chart, and standardization.